2007
DOI: 10.1213/01.ane.0000265552.43299.2b
|View full text |Cite
|
Sign up to set email alerts
|

Postoperative Analgesia After Knee Surgery: A Comparison of Three Different Concentrations of Ropivacaine for Continuous Femoral Nerve Blockade

Abstract: Ropivacaine 0.2% and 0.3% were similar in terms of analgesic quality. Initial infusion rates should be adjusted to 15 mL/h to obtain effective analgesia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
59
2
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(65 citation statements)
references
References 15 publications
3
59
2
1
Order By: Relevance
“…However, during the next 24 hours, both concentrations provided similar analgesia. Consistent with findings from a previous study on continuous femoral nerve blockade, 8 our results suggest that for continuous interscalene block after shoulder surgery, decreasing a ropivacaine concentration from 0.2% to 0.1% reduces the analgesic effectiveness of the technique.…”
Section: Discussionsupporting
confidence: 91%
“…However, during the next 24 hours, both concentrations provided similar analgesia. Consistent with findings from a previous study on continuous femoral nerve blockade, 8 our results suggest that for continuous interscalene block after shoulder surgery, decreasing a ropivacaine concentration from 0.2% to 0.1% reduces the analgesic effectiveness of the technique.…”
Section: Discussionsupporting
confidence: 91%
“…We agree that Brodner and colleagues [3] previously have concluded that ropivacaine 0.2% and ropivacaine 0.3% were equivalent in terms of pain outcomes compared to ropivacaine 0.1% when used as continuous infusion for femoral nerve blocks. However, Brodner and colleagues designed their study to test the hypothesis that ropivacaine 0.3% was superior to ropivacaine 0.2% or 0.1%, and the authors' conclusion that 0.1% was ineffective was based on an interim statistical analysis of only 20 patients.…”
supporting
confidence: 72%
“…[3][4][5] So far, attempts to reduce quadriceps involvement after femoral nerve block (FNB) without compromising analgesia have not succeeded. 1,[6][7][8] Unlike FNB, adductor canal block (ACB) is predominantly a sensory block, 9 which preserves quadriceps muscle strength and ambulation ability better than FNB. 2 A study in healthy volunteers showed that FNB reduced quadriceps strength by 49% from baseline, compared with only 8% with ACB.…”
Section: Resultsmentioning
confidence: 99%